The Contribution of Agility and Flexibility to the Dribbling Skills of Futsal Players at SMP Negeri 21 in Bengkulu City - Deigo Armando; Dody Ertanto; Roni Syaputra (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the contribution of agility and flexibility to the dribbling ability of futsal players at SMPN 21 in South Bengkulu City. Using a total sampling method, the study involved 16 futsal players at SMPN 21 in South Bengkulu City. This is a correlational study based on tests of agility, flexibility, and dribbling skills among futsal players at SMPN 21 in South Bengkulu City. Descriptive data analysis and correlation tests were employed. The results of this study indicate that there is a significant correlation between agility and the dribbling skills of futsal players at SMPN 21 in South Bengkulu City (rxy = 0.521), there is a significant correlation between flexibility and the dribbling skills of futsal players at SMPN 21 in South Bengkulu City (rxy = 4.574), and there is a significant relationship between agility and flexibility on the dribbling skills of futsal players at SMPN 21 in South Bengkulu City (calculated F = 4.511 > table F = 3.63).